Influence of soil spatial variability on the reliability of sandy slopes incorporating anisotropy and non-stationarity. - Li-Qun Zheng; Yuan Zhou; Lei Huang; Ling-Jun Huang; Xiao-Qiang Fu (PLoS ONE)
Influence of soil spatial variability on the reliability of cohesive soil slopes has been investigated extensively in the previous studies. However, it is seldom investigated for sandy slopes, especially incorporating anisotropy and non-stationarity. This paper explores the impact of the anisotropic spatial variation and non-stationary characteristics of soils on the reliability of sandy slopes. Specifically, two types of non-stationary random field (RF) are included, namely RF Type 1(soil strength increases along the depth) and RF Type 2 (strength increases along the direction perpendicular to bedding). For sandy slopes, the reliability index (β) is stable as the major autocorrelation distance of soil properties increases, and it decreases as the minor autocorrelation distance increases, which aligns with the observations for clay slopes. For slopes with horizontal bedding, the results of β under stationary RF are close to those under RF type 1. For dip-slopes and reverse-dip slopes with a 1:1 ratio, the difference between β under stationary RF and RF Type 1 is small. For dip-slopes with 1:2 ratio, this difference remains small, but for the reverse-dip slopes, it is significant. These findings differ from the previous studies on clay slopes, where the difference between β under stationary RF and RF Type 1 is significant for each slope scenario. Besides, β under RF type 2 is the smallest for dip slopes and reverse-dip slopes with ratio = 1:2, and it is the highest for reverse-dip slopes with ratio = 1:1.